Effect of different planting density of sunflower varieties on yield and yield attributing characters in rice-rice-sunflower cropping pattern - Nowrose Jahan Lipi; Muhammad Maniruzzaman (Research in Agriculture Livestock and Fisheries, 2024)
The experiments were carried out at the Agronomy Experimental Field of Patuakhali Science and Technology University, Dumki, Patuakhali in order to evaluate the effect of sowing date and planting density on the yield and yield contributing characters of sunflower varieties. The experiment comprised of two varieties viz. BARI Sunflower2 and Hysun33 and six planting densities viz. 40cm×25cm, 40cm×35cm, 40cm×45cm, 50cm×25cm, 50cm×35cm, 50cm×45cm. The experiment was laid out in a split-plot design with three replications, where the variety was assigned in the main plot and planting density was assigned as sub-plot treatment. Planting density had a significant influence on all the characteristics of morphological growth, yield, and yield contributing character except plant height at 75 DAS and 90 DAS. In case of Hysun33 variety, the highest number of leaves (21.89), leaf area (3214.22 cm2), head diameter (19.27 cm), head weight (539.07 gm), number of seed head-1 (973.33), seed weight head-1 (65.89 gm), thousand seed weight (67.73 gm), total seed yield (3.27 tha-1) and harvest index (34.30 %) was obtained from 50 cm × 45 cm planting density. On the other hand, in case of BARI Sunflower2 variety the highest number of leaves (18.44), leaf area (3342.90 cm2), head diameter (18.73 cm), head weight (457.80 gm), number of seed head-1 (832.17), seed weight head-1 (53.39 gm), thousand seed weight (64.07 gm) was obtained from 50 cm × 45 cm planting density and the highest stover yield (8.04 tha-1) and biological yield (10.73 tha-1) were obtained from 40 cm × 25 cm planting density. The highest total seed yield (2.94 tha-1) was obtained from 50 cm × 25 cm (8 plants m-2) planting density. Vol. 10, No. 3, December 2023: 229-235